Competitividad del Puerto de Santa Marta, Magdalena en los años 2016 al 2020 en el manejo de carga contenerizada. (2022)
In the present work, a comparative study of the activities in the primary customs zones of Colombia on containerized cargo during a period was carried out. Comparing the port of Santa Marta, with literature and data from reliable entities versus the ports of Barranquilla and Cartagena. To identify the competitiveness that the port of Santa Marta has or has acquired in the period 2016-2020 in the handling of containerized cargo. Three phases were applied in this research: starting with a data collection technique, in which academic literature was consulted. A second phase of verification with reliable entities related to the sector; and a final phase of analysis and results; comparing it with the diamond model of the economist Michael Eugene Porter, thus allowing to solve the questions raised in the formulation of this monograph.